1996
DOI: 10.1074/jbc.271.25.15292
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Specificity of the Fibroblast Growth Factor Family

Abstract: Fibroblast growth factors (FGFs) are essential molecules for mammalian development. The nine known FGF ligands and the four signaling FGF receptors (and their alternatively spliced variants) are expressed in specific spatial and temporal patterns. The activity of this signaling pathway is regulated by ligand binding specificity, heparan sulfate proteoglycans, and the differential signaling capacity of individual FGF receptors. To determine potentially relevant ligand-receptor pairs we have engineered mitogenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

51
1,346
5
26

Year Published

1997
1997
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 1,564 publications
(1,428 citation statements)
references
References 61 publications
51
1,346
5
26
Order By: Relevance
“…In addition, the diversity in the binding specificity of FGF receptors for FGFs clearly can lead to a large combinatorial set of possible interactions. It has been demonstrated that FGF3 activates the b splice forms of FGFRs 1 and 2 [Ornitz et al, 1996] and that FGFR2b binds to FGF10 [Yeh et al, 2003]. It is interesting to observe that increased risks of CL/P in our study were found for alleles in FGF3, FGF10, and FGFR2.…”
supporting
confidence: 51%
“…In addition, the diversity in the binding specificity of FGF receptors for FGFs clearly can lead to a large combinatorial set of possible interactions. It has been demonstrated that FGF3 activates the b splice forms of FGFRs 1 and 2 [Ornitz et al, 1996] and that FGFR2b binds to FGF10 [Yeh et al, 2003]. It is interesting to observe that increased risks of CL/P in our study were found for alleles in FGF3, FGF10, and FGFR2.…”
supporting
confidence: 51%
“…Four receptors have been detailed (designated FGFR 1 -4) and multiple splice variants of these receptors have been described (Ornitz et al, 1996). FGF8 is known to activate FGFR2, 3 and 4, as well as FGFR1 if applied in high concentrations (Ornitz et al, 1996;Blunt et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Four receptors have been detailed (designated FGFR 1 -4) and multiple splice variants of these receptors have been described (Ornitz et al, 1996). FGF8 is known to activate FGFR2, 3 and 4, as well as FGFR1 if applied in high concentrations (Ornitz et al, 1996;Blunt et al, 1997). In addition, developmental studies have shown that it is the c splice forms of FGFRs that are the preferred targets of FGF8 and these are expressed predominantly in the mesenchymal tissue (MacArthur et al, 1995b).…”
Section: Discussionmentioning
confidence: 99%
“…As it stands now, the FGF family comprises 10 characterized growth regulatory proteins that share 35 ± 50% overall homology (reviews in Basilico and Moscatelli, 1992;Goldfarb, 1996, and for FGF-10: Yamasaki et al, 1996). FGF-3 to 8 and FGF-10 are each synthesized with a signal peptide which transports them to the secretory pathway, whereas FGF-1, -2 and -9 which lack a signal peptide, are released from the cells by unknown mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…Four genes encode the high a nity receptors, FGFR-1 to -4, but alternative splicing generates at least 60 isoforms of the proteins. Thus, FGF-3 binds mainly to the IIIb isoforms of FGFR-1 and FGFR-2 (Mathieu et al, 1995) whereas FGF-4 binds to the IIIc isoforms of FGFR-1, -2 and -3 (Kanai et al, 1997) and to FGFR-4 (Ornitz et al, 1996;review in Goldfarb, 1996).…”
Section: Introductionmentioning
confidence: 99%